Las estampillas Ibérico-Latinas K.5.4 (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper studies bilingual ante cocturam stamps and stamps on mortaria in order to deepen the understanding of Iberian-Latin stamps MLH IV K.5.4
Keywords: Palaeohispanic Epigraphy; Pottery Stamps.; Bilingual Inscriptions; Mortaria.; Opus Doliare Manufacture